Mirror Mode Junctions as Sources of Radiation - Treumann, R. A.; Baumjohann, Wolfgang (Frontiers in Astronomy and Space Sciences, 2021)
Mirror modes in collisionless high-temperature plasmas represent macroscopic high-temperature quasi-superconductors with bouncing electrons in discrete-particle resonance with thermal ion-sound noise contributing to the ion-mode growth beyond quasilinear stability. In the semi-classical Ginzburg-Landau (GL) approximation the conditions for phase transition are reviewed. The quasi-superconducting state is of second kind causing a magnetically perforated plasma texture. Focussing on the interaction of mirror bubbles we apply semi-classical Josephson conditions and show that a mirror perforated plasma emits weak electromagnetic radiation which in the magnetosheath should be in the sub-millimeter respectively infrared range.